Changes in biochemical profiles of children with severe acute malnutrition on admission and after nutritional rehabilitation - Barman, Mithu; Rabha, Jolly; Rohman, Syeda Mohsina (Indian Journal of Child Health, 2024)
Purpose: The given study was done to find out the changes in biochemical profiles before and after nutritional rehabilitation of the children admitted at the Department of Paediatrics, Assam Medical College with severe acute malnutrition (SAM). Materials and Methods: A hospital based observational study was conducted from May 2020 to April 2021 with 55 consecutive cases of SAM. Vitros System 5600 was used for analysis of 13 biochemical parameters. Results: The mean values of serum sodium, potassium, and chloride at admission were 134.59±19.37 mEq/L, 4.22±0.80 mEq/L, and 101.12±16.36 mEq/L and that after rehabilitation were 136.66±19.95 mEq/L, 4.42±0.68 mEq/L, and 103.97±4.83 mEq/L. While that for magnesium, calcium, and phosphorous on admission were 2.11±0.38 mg/dL, 8.70±1.00 mg/dL, and 4.33±1.23 mg/dL and that after rehabilitation were 2.10±0.29 mg/dL, 9.45±0.65 mg/dL, and 4.76±0.84 mg/dL, respectively. The mean values of serum total protein, albumin, globulin, and A: G on admission were 6.53±1.44 g/dL, 3.30±0.88 g/dL, 3.23±0.87 g/dL, and 1.06±0.33, respectively, and that after rehabilitation were 6.84±0.98 g/dL, 3.86±0.57 g/dL, 2.98±0.69 g/dL, and 1.34±0.28, respectively. The mean of urea and creatinine on admission were found to be 26.25±19.30 mg/dL and 0.34±0.24 mg/dL, respectively, and that after rehabilitation were 23.91±11.76 mg/dL and 0.31±0.15 mg/dL respectively. Random blood sugar (RBS) on admission was 85.20±17.88 mg/dL and that after rehabilitation was 94.18±14.82 mg/dL. After rehabilitation, the mean value of calcium, phosphorous, albumin, A: G, and RBS were significantly raised. The minimum duration required for rehabilitation was 12 days with prevalence being maximum among the Tea-tribes (80.00%). Conclusion: The biochemical derangements in a patient with SAM are associated with significant morbidity and get improved after nutritional rehabilitation.